2007
DOI: 10.1002/pd.1815
|View full text |Cite
|
Sign up to set email alerts
|

Preconceptional and prenatal screening for fragile X syndrome: Experience with 40 000 tests

Abstract: There is now sufficient information on screening parameters and prenatal diagnosis of fragile X syndrome to offer testing to women of reproductive age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
95
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 15 publications
9
95
1
1
Order By: Relevance
“…In two earlier observational studies, which included large cohorts of unselected women, the prevalence of premutations and full mutations during their reproductive age span was shown to vary between 1.43 24 and 0.5%, 25 whereas among women with close relatives suffering from fragile X syndrome and diagnosed with POI, the prevalence rate of the full mutation was reported to be as high as 16.8% and that of the premutation as high as 52%. 14 By contrast, among women with POI but without cases of the fragile X syndrome among close family members, the prevalence of full mutations and premutations was much lower, with the latter varying from 2.2 26 and 2.5 27 to 4.9%.…”
Section: Discussionmentioning
confidence: 98%
“…In two earlier observational studies, which included large cohorts of unselected women, the prevalence of premutations and full mutations during their reproductive age span was shown to vary between 1.43 24 and 0.5%, 25 whereas among women with close relatives suffering from fragile X syndrome and diagnosed with POI, the prevalence rate of the full mutation was reported to be as high as 16.8% and that of the premutation as high as 52%. 14 By contrast, among women with POI but without cases of the fragile X syndrome among close family members, the prevalence of full mutations and premutations was much lower, with the latter varying from 2.2 26 and 2.5 27 to 4.9%.…”
Section: Discussionmentioning
confidence: 98%
“…The number of repeats causing FXS is ≥200 (full mutation), while the 'normal' range is 6-44 repeats, and 55-200 repeats is the premutation range (i.e., carrier of FXS) (Fu et al 1991;Snow et al 1993). The length of the CGG repeat is unstable over a certain size such that a premutation can expand to a full mutation when passed onto offspring through female, but not male, carriers (Fu et al 1991;Berkenstadt et al 2007;Nolin et al 1996). Therefore, carrier screening in primary care for reproductive risk in women is more relevant as male carriers are not at risk of having children affected with FXS.…”
Section: Carrier Screening For Fragile X Syndromementioning
confidence: 99%
“…Some large-scale screening studies have found that the premutation frequency in females is 1 in 549 in Canada (Lévesque et al 2009), 1 in 158 in Israel (Berkenstadt et al 2007) and 1:179 in USA on non-selected individuals (Hantash et al 2011). Carrier frequency may be different again in other population groups, with no carriers found in 370 women screened in a Japanese study (Otsuka et al 2010) and 1,002 women from Taiwan (Huang et al 2003), although these were much smaller sample sizes.…”
Section: Carrier Screening For Fragile X Syndromementioning
confidence: 99%
See 2 more Smart Citations